(untitled) (Principles and Practice of Clinical Research, 2022)
Introduction: The COVID-19 pandemic prompted policies that limited direct human interactions globally. Due to this, healthcare systems worldwide have witnessed unprecedented challenges in providing adequate and continuous healthcare for patients with Non-Communicable Diseases (NCDs), among them hypertension and diabetes. The pandemic promoted the expansion of telehealth, thanks to its potential to extend services to remote places and capitalize on high expertise made available to patients otherwise kept waiting or unattended. Despite this, few studies have analyzed health professionals' evaluation of telehealth usability for post-pandemic care of patients with NCDs. Objective: To assess healthcare professionals' evaluation of telehealth usability in post-pandemic care of patients with NCDs.Methods: This is a systematic review and narrative analysis. The primary outcome will be usability or "ease of use" in patient care. Secondary outcomes are satisfaction (acceptance), the impression of their patient's satisfaction, and the contexts in which the mobile devices are used. Clinical trials, prospective cohort studies, retrospective observational studies, and studies that used qualitative data collection and analysis methods, published in English, Spanish or Portuguese from March 2020 onwards, on healthcare professionals' evaluation of telehealth in post-pandemic care of patients with hypertension and diabetes will be included. Studies that do not pertain to the research questions, incomplete articles, abstracts, review articles, editorials, books, academic articles, dissertations, theses, and proceedings of scientific events will be excluded. The databases to be queried will be MEDLINE (accessed by PubMed), Embase, BIREME, IEEE Xplore, gray literature, and manual search. Key words: healthcare professional; telehealth; non-communicable disease; usability COVID-19 Pandemic